(untitled) (World Science, 2019)
Antitrust, which provides a key way to identify the driving forces for self- development and the development of speech behavior have been examined in this article. Some aspects of the influence of antitrust in the social interaction of the child with the environment in various situations of uncertainty and familiar content, the importance of creative achievements of the communicative-speech development of the senior preschooler on the growth of conscious self-regulation of linguistic behavior have been confirmed here. It has been proved that one of the lines of personal potential development is the speech behavior of the child and the presence of creative driving force - antitrust, aimed at creating of the future result of the interaction and making decisions on the subsequent course of the communicative situation based on this image. It has been affirmed that the general mental development of the child, the formation of «preschool maturity» is the base ground for the manifestation of creativity, in particular in communicative activities and the development of antitrusting capabilities of the child as a manifestation of «anticipation of the future», designing as creative prediction, creating images of future activities. It has been made a conclusion concluded that inheritance of cultural traditions, although it provides a person with a tool for the implementation of linguistic communication, but without forming a creative imagination destroys effective meaningful personality traits: integrity, uniqueness, activity, expression, openness, self-development, self-regulation.